2015
DOI: 10.1186/s12905-015-0198-x
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and psychological characteristics of women seeking multiple abortions in the region of Monastir (Tunisia): results of a cross-sectional design

Abstract: Background: Repeat abortion is a public health concern favored by many obstetric and social factors. The purpose of our study was to identify associated factors to repeated abortion in the region of Monastir (Tunisia). Common mental disorders (CMD) such as anxiety and depression were also evaluated in women seeking voluntary repeated abortion. Methods: We carried out a cross sectional study between January and April 2013 in the Reproductive Health Center (RHC) of the region of Monastir in Tunisia (This study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
14
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 26 publications
8
14
4
2
Order By: Relevance
“…Finally, those who had a history of physical violence by a male partner had a 2.6 times higher risk of having a RIA than those who did not have a history of physical violence. This result is consistent with the studies done in Tunisia [15]. This could be due to fear of telling her male partner about the pregnancy and tend to protect herself by having an induced abortion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, those who had a history of physical violence by a male partner had a 2.6 times higher risk of having a RIA than those who did not have a history of physical violence. This result is consistent with the studies done in Tunisia [15]. This could be due to fear of telling her male partner about the pregnancy and tend to protect herself by having an induced abortion.…”
Section: Discussionsupporting
confidence: 92%
“…Our study has identified that participants who had no education and had an educational level of primary and secondary were more likely to undergo a RIA than those who had an educational level of more than secondary. The finding is in consistent with the study in Ethiopia, Kenya, Tunisia, Georgia, and Russia [1,8,15,18,19]. Unplanned pregnancy secondary to poor contraceptive knowledge and use among those with a lower educational level might be the possible reason.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There has been an increasing number of studies that investigated factors associated with health-seeking behaviors of mothers and children [13]. Similar findings across these studies suggested that maternal health care is generally affected by various personal, sociocultural and environmental factors, including individual perceptions of health, self-efficacy, motivation, social values and belief systems [14][15][16]. Access to SBA services are found to be associated with various sociodemographic factors, for example education of women/mothers, religion, residency (urban/rural) and household financial capabilities are important predictors for women's access to maternal health services [17][18][19][20].…”
Section: Introductionmentioning
confidence: 83%
“…Research evidence from other South Asian countries suggests that men’s involvement in women’s reproductive care has a crucial role to play to increase the uptake of maternal health services and reduce maternal and infant mortality [1214]. Reproductive health seeking behaviour of an individual has shown to be a psychological construct affected by various proximal/individual (perception of health, self-efficacy, motivation) [12, 14, 15] and distal/social influences (social norms and values, belief systems, degree of openness about personal matters) [16, 17]. There is also lot to accomplish especially in the areas of universal access to reproductive health services, increasing the rate of institutional delivery and adoption of family planning which have shown to be more effective in active presence of male counterparts [15, 18].…”
Section: Introductionmentioning
confidence: 99%